Pengaruh Kualitas Produk, Kualitas Pelayanan, dan Kenyamanan Pelayanan terhadap Kepuasan Konsumen Rumah Makan Soto Mas Boed Semarang - Alvina Ayu Septianingrum; Ida Martini (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This study aims to analyze "The Effect of Product Quality, Service Quality, and Convenience on Consumer Satisfaction at Soto Mas Boed Restaurant Semarang". The data collection method uses a questionnaire. The sampling technique uses accidental sampling technique. A sample of 97 respondents were consumers at the Soto Mas Boed Restaurant in Semarang. Based on the test results, the product quality variable has a positive and significant effect on customer satisfaction. This is evidenced by the regression coefficient of β1 0.264 and the calculated t value is greater than the t table 3.751> 1.661 with a sig. value of 0.000 <0.05. So the hypothesis is proven. Service quality has a positive and significant effect on customer satisfaction. This is evidenced by the regression coefficient of 0.482, the t value is greater than the t table 4.934> 1.661 with a sig. value of 0.000 <0.05. So the hypothesis is proven. Convenience has a positive and significant effect on consumer purchasing decisions. This is evidenced by the regression coefficient of 0.229, the t value is greater than t table 2.616> 1.661 and the sig value is 0.010 <0.05. So the hypothesis is proven.